Kisruh Sengketa Sertifikat Ganda Di Bekasi: Menilisik Peran Hukum Acara Perdata Dalam Menjamin Keadilan - Layya Iksiru Ghilma; Andika Adhitama; Zaskia Madina (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
In the case of dual certificate disputes in the Bekasi area, it illustrates the complexity of an agrarian issue in Indonesia that not only affects one aspect of land ownership rights.However, it will create legal uncertainty for the affected community.The purpose of this research is to investigate or examine the role of civil procedural law in a case of resolving a double certificate dispute in order to ensure justice for the disputing parties.This research method uses a normative juridical approach with a case study through the analysis of court decisions related to a double certificate dispute case in the Bekasi area.The research results indicate that the application of civil procedural law in the double certificate dispute has not been fully effective in providing legal certainty and justice.Factors such as inconsistent legal interpretations, lack of coordination between institutions, and numerous land mafia practices further exacerbate the resolution of such disputes.Therefore, it is essential to strengthen the civil procedural law system, enhance the capacity and quality of judges, and improve the land administration system to minimize the potential for double certificate disputes in the future.This study then concluded that in ensuring dual land certificates, there are two types of legal protection: preventive and repressive.Preventive protection allows the community to express their opinions or voice their concerns before the government's decision becomes final.Repressive protection allows the community to resolve existing issues.Land disputes can be resolved through litigation or nonlitigation channels.The first involves negotiation, conciliation, mediation, and arbitration.